Profitabilitas Memediasi Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan Subsektor Food And Beverage - Carolyn, Callysta; Indah, Nopiani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to analyze the extent to which capital structure and firm size influence firm value through profitability as a mediating variable in the food and beverage sector listed on the Indonesia Stock Exchange. The study involved 95 companies, with 47 companies selected as the research sample using purposive sampling technique. The statistical analysis approach was conducted using EViews 13 software. Data analysis employed the Fixed Effect Model, along with classical assumption tests (multicollinearity and heteroscedasticity tests), hypothesis testing (coefficient of determination, multiple linear regression, F-test, and t-test), and the Sobel test. The findings of the study indicate that capital structure on profitability is 0.00 <0.05 with a t-statistic of -8.67 and company size on profitability with a probability result of 0.00 <0.05 and a t-statistic of -3.09, this states that capital structure and company size have a negative effect. Other research results also revealed that capital structure and profitability have a positive effect on company value, with the results of the probability of capital structure being 0.00 <0.05 and t-statistic 6.66 and the probability of profitability being 0.00 <0.05 and t-statistic 5.91. While company size has no effect on company value with a probability of 0.1873> 0.05 and t-statistic 1.32. In the Sobel test, it was stated that the results of profitability were able to mediate capital structure and company size on company value, while the test results on the capital structure variable were -4.88> t-table and company size were -2.74> t-table.